Improving Communication Skills in Clinical Education of Nursing Students - Haydeh Heidari; Marjan Mardani Hamooleh (Iran University of Medical Sciences, 2015)
Background: Effective communication with patients is an essential part of nursing care. However, most researches have reported that communication of nurses with patients is weak. The quality of provided care, especially communication with the patients, is one of the main concerns of nursing education managers. Therefore, we conducted a study with the aim of improving communication skills in clinical education of nursing students.  Methods: This research is a qualitative study, which was conducted in pediatric unit of Hajar Hospital, Shahrekord, Iran. Purposive sampling was used in this study whose participants were 8 nursing students (Sixth-semester) studying in the pediatric ward. Students' experiences with this communication method were analyzed using qualitative content analysis. Data collection continued until that information was repetitive. The data were saturated after 8 participants were interviewed.  Results: Based on the analysis of students' experiences, 3 main categories of unfamiliarity with methods of communicating with patients, appeal of the interviewing method, and obstacles to communication with patients were found.  Conclusion: The results of the study indicate that proper use methods of communication improved nurses' ability to communicate with patients. It is recommended to add communication skills and interview techniques as an applied course in the undergraduate curriculum.